Blueing reflectivity integration (BRI) for seismic spectral enhancement and its application in seismic data interpretation - Babasafari, A.A. (Slovnaft VURUP a.s, 2019)
Enhancing seismic data resolution through broadening frequency bandwidth aids to reveal sub seismic, geological features. There are some approaches which try to overcome this limitation in different stages of seismic data analysis from acquisition to processing and interpretation. Some of these techniques boost high frequency noises. Hence, to mitigate generating pitfall reflectors in seismic data, the algorithm is preferred from which seismic vertical resolution is enhanced with less side effect of boosting noise. A new and practical technique is proposed by incorporating seismic and well data. Blueing Reflectivity Integration (BRI) technique helps to create a new seismic data set that can disclose thin beds below seismic tuning thickness. Using seismic and acoustic impedance log, an operator is designed and convolved with seismic data reflectivity series to produce enhanced seismic data. The more appropriate match between seismic and synthetic data in well to seismic tie process demonstrates the efficiency of this approach for seismic resolution enhancement. The BRI volume reduces uncertainties in seismic data interpretation. For this purpose, its applications in RGB blended display for structural-stratigraphical interpretation and also hydrocarbon prediction in reservoir characterization are analyzed and compared with original seismic data. Â© 2019